Management Teachings and Ethos of different Sikh Gurus: Exploring the Management Teachings and Ethos of Sikh Gurus (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Different Sikh Gurus which are considered the spiritual master of Sikhism, have given different ethos and teachings related to management time to time. These Gurus are considered the holy leaders and teachers of Sikhs. The credit goes to Guru Nanak that he introduced real reforms and laid the foundation on which his successor, the tenth Sikh Master, Guru Gobind Singh created a new nation. Guru Nanak saved his followers from those shortcomings to which the disciples of many other religions had been falling prey to for centuries. He taught the people worship of God and purity of character. In this way, he started a new religion which was simple, independent, non-communal and free from rites and rituals (Cunningham, 1994)This paper evaluates the ethics and ethos in management and the teaching of different Sikh Gurus related to Management in modern era. Generally, management is the process of optimum utilization of human and non-human resources along with the values to achieve some goals at individual level or an organizational level. In the Business world, management is defined as a process of managing various resources such as people, finance and technology to achieve organizational goals. It also ensures that resources are developed and utilized in such a manner that both short term as well as long term goals can be achieved very effectively and efficiently. A country like India whose culture has its roots in religion, draw its lessons from the religion of the land –be it Hinduism, Buddhism, Sikhism or any other. In same manner Ethos of modern management also evolves the basic principles as immense potential, holistic approach, internal resources, Karm yoga, yoga Karmasu Kaushalam and co-operation. The Holy Epic of Shri Nank Dev ji is a remarkable storehouse of spiritual knowledge and its teachings stress on the name of God. Guru Nanak Dev Ji states all the principles of management in the Mool Mantra and can enable men and women to lead a purposeful and rewarding life while being members of a society. It teaches that we are Karma Yogis, hence we reap what we sow.